Fertility-enhancing effect of oil-based contrast agents during hysterosalpingography and the variation of this effect within a 3-year follow-up period in infertile patients - Lu, Jingyuan; Qi, Dan; Xu, Wenjian (Frontiers in Medicine, 2022)
Objective The previous study has indicated the fertility-enhancing effect of oil-based contrast agents during hysterosalpingography (HSG) in infertile patients. However, the variation of this effect with the time frame is seldom reported. The current study aimed to explore fertility improvement using oil-based contrast agents and the change of this improvement during the 3-year follow-up period in infertile patients. Materials and methods Infertile women who underwent HSG with oil-based contrast agents (N = 500) or water-based contrast agents (N = 500) were enrolled. Spontaneous pregnancy rate and time to pregnancy were assessed at months (M)1, M2, M3, M6, M12, M24, and M36 after HSG. Results The spontaneous pregnancy rate was 79% in the oil-based group and 70.2% in the water-based group. The cumulative spontaneous pregnancy rate was increased in the oil-based group when compared with the water-based group (p = 0.015). Fertility-enhancing effect of HSG was increased in the oil-based group when compared with the water-based group at all time points {M1 [odds ratio (OR)]: 1.536}; M2 (OR: 1.455); M3 (OR: 1.494); M6 (OR: 1.356); M9 (OR: 1.288); M12 (OR: 1.249); M24 (OR: 1.131); and M36 (OR: 1.125). While this superiority of the fertility-enhancing effect of HSG in the oil-based group (vs. the water-based group) was decreased with the time frame. Similar findings were also observed based on the physiological cycles. Conclusion The HSG procedure with oil-based contrast agents shows a fertility-enhancing effect when compared to water-based contrast agents. This improvement could last at least 1 year while dropping to the normal level within the subsequent 2 years.